2021
DOI: 10.5603/fc.a2021.0053
|View full text |Cite
|
Sign up to set email alerts
|

Czy wynik CHA2DS2-VASc determinuje leczenie przeciwzakrzepowe u pacjentów z migotaniem przedsionków? Dane z POLish Atrial Fibrillation (POL-AF) Registry?

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…We did not observe differences in a thromboembolic risk assessed based on CHADS 2 and CHA 2 DS 2 -VASc between OAC-treated and untreated groups. Similarly, Szpotowicz et al [ 21 ] found that the CHA 2 DS 2 -VASc score did not predict OAC use in the studied cohort of patients with AF.…”
Section: Discussionmentioning
confidence: 78%
“…We did not observe differences in a thromboembolic risk assessed based on CHADS 2 and CHA 2 DS 2 -VASc between OAC-treated and untreated groups. Similarly, Szpotowicz et al [ 21 ] found that the CHA 2 DS 2 -VASc score did not predict OAC use in the studied cohort of patients with AF.…”
Section: Discussionmentioning
confidence: 78%